The Production Characteristics of Male Bandicoot (Echymipera kalubu) - Frandz Rumbiak Pawere; Desni Triana Saragih (Buletin Peternakan, 2019)
The aim of this research is to understand the production characteristics of male bandicoot (Echymipera kalubu) and obtain basic morphometric information for cultivation and development of the animal. The research was done through the explorative method by using 30 random undomesticated adult male Echymipera kalubu obtained in Manokwari regency forest, West Papua. The morphometric characteristics of Echymipera kalubu in regards to the body weight and carcass weight are yet to be observed and standardized for practical use. The obtained estimator variables were analyzed by SPSS 24 for windows to calculate the multiple regression and coefficient of correlation value. The results of statistical analysis showed that there were 4 estimator variables that had positive correlations, which were body length (X1), hind legs length (X2), heart girth (X4), and cannon girth (X5). The obtained body weight regression formula was Y1 = -1367.355 + 33,912X1 + 7,095X2 + 89,745X4 – 14,494X5 with the coefficient of determination at 0.815. Moreover, the obtained carcass weight regression formula was Y2 = -1282,170 + 40,113X1 + 7,666X2 + 66,750X4 - 24,231X5 with the coefficient of determination at 0.794. The research concluded that the best estimator variable for body weight and carcass weight was the heart girth.